The political economy of populism: An agenda-theoretic approach with special reference to Germany - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2023)
Populism in modern Western democracies is on the rise. The existing literature concentrates on explanations based on the growing socio-economic and socio-cultural polarisation of modern societies driven by globalisation and individualisation on the one hand and the unresponsiveness of unrepresentative governments and non-majoritarian bodies on the other hand. Although such explanations certainly contribute partly to our understanding of the phenomenon called 'populism' - particularly the (right or left-wing) extremist dimension of it -, it does not sufficiently explain the seemingly non-ideological 'populism of the middle class' which, at least in Germany, accounts for the bigger, yet less visible part of populism. The objective of the paper is to focus on systematic weaknesses of collective decision-making in liberal-representative democracies in explaining populism (particularly of the middle class) as a growing critique of the institutions of liberal democracy.
Keywords: D70; D72; H40; P10; P5; 330; Populism; liberal democracy; political economy; minority rule; elites